Limits for Coregonus migratorius (Georgi, 1775) catches and likely ecological effects - P. N. Anoshko; M. M. Makarov; V. I. Zorkaltsev; N. N. Denikina; E. V. Dzyuba (Юг России: экология, развитие)
Aim. This study aims to discuss the validity of introducing restrictions on the catch of Coregonus migratorius (Georgi, 1775) with a forecast of the likely environmental consequences of doing so.Discussion. We show the results of the analysis of the assessment of the state of C. migratorius stocks and the reasons for their decline. We indicate that the biostatistical and hydroacoustical methods for estimating fish numbers, which are traditionally used to substantiate allowable catches, have some disadvantages and limitations. We consider unrecorded catches and unfavourable natural and climatic environmental factors to be reasons for the decline in C. migratorius stocks. We discuss ecological and anthropogenic factors of changes in stocks of this commercially important species for the region. We show the anticipated ecological effects of currently established limits.Conclusion. The results of changes in the modelling of the number and age composition of fish with different protection strategies indicate that maintaining a low level of replenishment stock the limits would not increase commercial stocks of C. migratorius. Restrictions imposed on the commercial and amateur fishing would significantly increase environmental risks through increase of poaching (including during the spawning period) as well as as a consequence of amateur fishing of other commercially valuable fish species.